Does Atopy Influence the Effectiveness of Treatment of Adenoid Hypertrophy with Mometasone Furoate?. Issue 1 (January 2015) - Rezende, Renato M.; Amato, Flávia S.; Barbosa, Aline P.; Menezes, Ulissis P.; Rezende, Patrícia; Ferriani, Virgínia P.L.; Anselmo-Lima, Wilma T.; Valera, Fabiana C. P.
Background: The effect of topical mometasone for adenoid hypertrophy treatment is well established. Nevertheless, the influence of atopy on this treatment remains ill defined. Objective: This study aims to compare the effects of topical mometasone furoate treatment on the adenoid tissue between atopic and nonatopic children. Methods: Fifty-one children with obstructive respiratory complaints underwent a semistructured clinical questionnaire on nasal symptoms, prick test, and nasoendoscopy. Nasoendoscopic images were digitalized, and both adenoid and nasopharyngeal areas were measured in pixels; the relative adenoid/ nasopharyngeal area was calculated. Patients were initially treated for 40 days with nasal saline solution. In a subsequent 40-day period, topical mometasone furoate (total dose, 100 μg/day) was used. Results: Topical mometasone significantly improved nasal obstruction, snoring, and apnea and also significantly reduced the adenoid tissue area related to the nasopharynx (p < 0.0001). Treatment with this glucocorticoid was not influenced by atopy, neither for symptoms nor for adenoid area. Conclusion: Topical mometasone furoate significantly reduced the adenoid tissue area and led to a supplementary improvement ofnasal symptoms. This improvement was similar for atopic and nonatopic patients.